2007
DOI: 10.1111/j.1469-8137.2007.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid alteration of cellular redox homeostasis upon exposure to cadmium and mercury in alfalfa seedlings

Abstract: Summary• Here, the kinetics of oxidative stress responses of alfalfa ( Medicago sativa ) seedlings to cadmium (Cd) and mercury (Hg) (0, 3, 10 and 30 µ M ) exposure, expanding from a few minutes to 24 h, were studied.• Intracellular oxidative stress was analysed using 2 ′ ,7 ′ -dichlorofluorescin diacetate and extracellular hydrogen peroxide (H 2 O 2 ) production was studied with Amplex Red. Growth inhibition, concentrations of ascorbate, glutathione (GSH), homoglutathione (hGSH), Cd and Hg, ascorbate peroxidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
95
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(112 citation statements)
references
References 42 publications
17
95
0
Order By: Relevance
“…therein). Cd 2+ -induced H 2 O 2 might be produced by plasma membrane NADPH oxidase (Garnier et al, 2006;Ortega-Villasante et al, 2007) or originate in mitochondria and then diffuse to other parts of the cells and in the apoplastic space (Heyno et al, 2008). The plant response to Cd 2+ in terms of antioxidant activities varies greatly, depending on the enzyme, the plant species, the tissue analyzed, the plant age, the intensity of the Cd 2+ treatment, and its duration (Schutzendubel and Polle, 2002).…”
Section: Exposure To CDmentioning
confidence: 99%
“…therein). Cd 2+ -induced H 2 O 2 might be produced by plasma membrane NADPH oxidase (Garnier et al, 2006;Ortega-Villasante et al, 2007) or originate in mitochondria and then diffuse to other parts of the cells and in the apoplastic space (Heyno et al, 2008). The plant response to Cd 2+ in terms of antioxidant activities varies greatly, depending on the enzyme, the plant species, the tissue analyzed, the plant age, the intensity of the Cd 2+ treatment, and its duration (Schutzendubel and Polle, 2002).…”
Section: Exposure To CDmentioning
confidence: 99%
“…In spite of that Cd is a non-redox-active metal; its toxicity is undoubtedly connected with increased levels of ROS. An enhanced level of lipid and protein peroxidation, increased level of ROS and activation of antioxidant apparatus indicated that in HM-stressed roots the presence of oxidative stress is a general syndrome in several plant species (Hegedüs et al 2001;Schützendübel et al 2001;Ranieri et al 2005;Garnier et al 2006;Rellán-Á lvarez et al 2006;Rodríguez-Serrano et al 2006;Ortega-Villasante et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports exist on oxidative stress and defence mechanisms in plants under arsenic stress [99][100][101][102]. Arsenic generates reactive oxygen species (ROS) during the reduction of As V to As III , which is followed by methylation, a redox driven reaction that may give rise to ROS [103].…”
Section: Arsenic Induced Oxidative Stress and Response In Rice Plantmentioning
confidence: 99%